Style of perception of parental relationship and coping in girls and teenagers with diagnosis of Turner’s syndrome - Aguilar, María José; López, Marcela Carolina; Urquijo, Sebastián (Anales de Psicología / Annals of Psychology, 2011)
Objectives. The difficulty of women with diagnosing of Turner syndrome to interact with peers is a characteristic widely described in literature, is usually associated with low self-esteem, emotional immaturity and social anxiety. Under the assumption that girls and adolescents with this diagnosis may be exposed to models of compensatory parenting developing distinctive forms of social interaction, the aim of this paper is to characterize the perception of parenting styles and coping in situations of social interaction in this population. Materials and methods. This was applied Argentine Coping Questionnaire and the Argentine Scale of Perceived Relationship with Parents- mother version- a sample of six children and adolescents diagnosed with Turner syndrome. Results. The results indicate a strong tendency to perceive the relationship with their mothers as democratic, based on the acceptance and use of functional strategies: logical analysis, search of support and cognitive restructuring. These characteristics are similar to those reported to the Argentine population. One possible explanation for these results could be due to the particular psychosocial characteristics of the approached sample.